User Experience Analysis of the Tomoro Coffe Application using the UEQ Method and SmartPLS - Muhammad Farhan; Apriansyah Putra; Ari Wedhasmara; Pacu Putra (SISTEMASI, 2026)
The rapid development of digital technology has encouraged food and beverage service providers to offer mobile applications that deliver an optimal User Experience (UX). This study aims to analyze the User Experience of the Tomoro Coffee application using the User Experience Questionnaire (UEQ) and examine the influence of the six UEQ dimensions on User Experience using SmartPLS 4. A quantitative approach was employed involving 97 respondents who had used the Tomoro Coffee application. Data were analyzed using the UEQ Data Analysis Tool and SmartPLS 4.The UEQ results indicate that Dependability (1.702) falls into the Excellent category, while Efficiency (1.854), Perspicuity (1.795), and Attractiveness (1.635) are categorized as Good. Meanwhile, Stimulation (0.955) and Novelty (0.399) are categorized as Below Average. The SmartPLS analysis shows that all UEQ dimensions have a positive and significant effect on User Experience, with Dependability having the strongest influence, followed by Efficiency, Attractiveness, Perspicuity, Stimulation, and Novelty. The novelty of this study lies in the integration of UEQ and SmartPLS 4, enabling the evaluation to not only measure UX levels through UEQ benchmarks but also empirically validate the contribution of each UEQ dimension to User Experience. The findings provide a more comprehensive evaluation framework and serve as an empirical basis for determining application development priorities based on the most influential UX dimensions.